1999
DOI: 10.1093/treephys/19.12.815
|View full text |Cite
|
Sign up to set email alerts
|

Above- and belowground biomass and net primary productivity of a Larix gmelinii stand near Tura, central Siberia

Abstract: We assessed above- and belowground biomass and net primary production (NPP) of a mature Larix gmelinii (Rupr.) Rupr. forest (240-280 years old) established on permafrost soils in central Siberia. Specifically, we investigated annual carbon budgets in roots in relation to root system development and availability of soil resources. Total stand biomass estimated by allometry was about 39 Mg per ha. Root biomass (17 Mg per ha) comprised about 43% of total biomass. Coarse root (>/= 5 mm in diameter) biomass was abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 24 publications
5
70
2
1
Order By: Relevance
“…The mean root-shoot ratio of our plots was 0.28 in the present study; however, for larch species growing in the permafrost region of Siberia, it ranges from 0.38 to 0.67 irrespective of fine roots [35], when incorporating fine roots it can reach 0.75 [36]. This strongly indicates that the species allocates more biomass to root in colder sites, namely, the root-shoot ratio increases latitudinally [37].…”
Section: Discussioncontrasting
confidence: 62%
“…The mean root-shoot ratio of our plots was 0.28 in the present study; however, for larch species growing in the permafrost region of Siberia, it ranges from 0.38 to 0.67 irrespective of fine roots [35], when incorporating fine roots it can reach 0.75 [36]. This strongly indicates that the species allocates more biomass to root in colder sites, namely, the root-shoot ratio increases latitudinally [37].…”
Section: Discussioncontrasting
confidence: 62%
“…The gradient in nutrient availability among sites is probably also reflected in C allocation among below-and aboveground biomass. For our study region, Kajimoto et al [37] reported that larch trees growing on the poorlydrained and colder soils of TB had a two-fold higher root-to-shoot ratio (1.13) in comparison to sites with a deeper active layer depth (i.e., <0.5). Such patterns are likely explained by an increasing competition belowground for accessible resources within a limited soil volume.…”
Section: Nutrient Status Of Larch Improves With Active Layer Depthmentioning
confidence: 77%
“…The latter accounts for the dominant part of the net primary productivity P 1 (g C m −2 per year) (Whittaker and Marks, 1975;Kajimoto et al, 1999). The turnover time τ 1 of the metabolically active plant biomass can be therefore estimated as τ 1 ≈ B 1 /P 1 .…”
Section: Discussionmentioning
confidence: 99%